Equity Judgments: Context Effects in Gains and Losses - Reyes-Contreras, Raul (2022)
Background: Previous studies have evaluated mathematical models of equity judgments of two hypothetical employees with distinct merits. They found that the model of proportionality adequately described the data based on an algebraic additive rule of information integration. Nevertheless, there is a lack of evidence concerning the effect of a context of monetary losses on the rules of information integration. Objective: To assess the effect of monetary gains and losses on equity judgments, and the effect of the personal context in which the participants are involved in decision-making. Method: A repeated measures design with within-subjects factors was utilized: 7 levels of A’s merit x 5 levels of B’s merit x 2 contexts (gains and losses) x 2 between-subject factors (third-party allocation and self-allocation). Results: Statistically significant differences appeared between thirdparty allocation and self-allocation conditions for gains [F (1,38) = 216.18, p < .001, η2P = .85] and losses [F (1,38) = 110.45, p < .001, η2P = .71]. Conclusions: The additive rules of integration appeared in the gains scenario while the subtractive rules together with an aversion to inequity were observed in the losses context. Authorship Contribution RRC: Conception and design of the study, collection and interpretation of data, discussion, and final revision of the manuscript. CSV: Interpretation of data, discussion, and final revision of the manuscript.